Surface fractal dimension: An indicator to characterize the microstructure of cement-based porous materials - Zeng, Qiang; Luo, Mingyong; Pang, Xiaoyun; Li, Le; Li, Kefei (Applied surface science, 2013)
[Display omitted] •Scale-dependent fractal property is confirmed for cement-based porous materials.•Micro-fractal and macro-fractal regions are identified for whole pore size range.•Upper pore size for micro-fractal range is around 30nm and nearly constant.•Curing condition and GGBS have impact on fractal properties of materials. This study investigates the surface fractal dimensions (SFDs) of pore structure of cement pastes and mortars with/without ground granulated blast-furnace slag (GGBS) incorporated into binder. The samples were subject to water curing and sealed curing. The fractal dimensions of samples are determined by Zhang’s model (Ind Eng Chem Res, 34 (1995):1383–1386) on the basis of mercury intrusion porosimetry (MIP) data. The results confirm the scale-dependent property of fractal dimension of pore structures and the micro-fractal, transition and macro-fractal regions are identified for all samples. The upper pore size range for micro-fractal regions is around 30nm, the transition regions cover 0.5–2 magnitude orders of pore size and macro fractal regions cover 1.5–3 magnitude orders. Both curing conditions and GGBS in binder have impact on the fractal properties of pore structure, and samples incorporating GGBS have substantially larger values for micro-fractal regions.